Tinjauan Yuridis Keberatan Ganti Kerugian Pengadaan Tanah Untuk Kepentingan Umum: Studi Putusan Hakim PN Batang Nomor: 23/ Pdt.G/2023/PN Btg - Rinaryanta, Nugroho Dwi; Lutfi, Anas; Sadino, Sadino (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Land acquisition or land release for infrastructure development aims to support the improvement of public welfare. However, disputes often arise regarding the amount of compensation paid to landowners. Parties who feel disadvantaged may pursue legal remedies by filing an objection or lawsuit concerning the compensation to the district court. This study aims to examine the juridical aspects of filing objections against compensation by referring to the decision of the Batang District Court, Case No. 23/Pdt.G/2023/PNBtg. The research uses a normative legal method through legislative and case study approaches. The findings show that filing objections to compensation depends on the fulfillment of both formal and material requirements as stipulated in tort claims. These requirements are illustrated in Article 1365 of the Indonesian Civil Code, which plays a key role in regulating the process. Affected communities in land acquisition processes have the right to justice, legal certainty, and legal protection.